Dynamics of dissolved inorganic carbon (DIC) and stable C isotope ratios (δ13CDIC) in a tropical watershed with diversified land use in São Paulo State, Brazil - da Conceição, Fabiano Tomazini [UNESP]; Fernandes, Alexandre Martins [UNESP]; Moruzzi, Rodrigo Braga [UNESP]; Mortatti, Jefferson (Elsevier, 2024)
The fluvial transport of dissolved inorganic carbon (DIC) is an important component of the global carbon cycle. Herein, we assessed the dynamics of DIC and the C stable isotopic composition (δ13CDIC) in a watershed with diversified land use in São Paulo State (Brazil), more specifically in the Sorocaba River basin (SRB) and considered the temporal and spatial scales. For this purpose, twelve fluvial samples at each sampling point (e.g., S1, S2, S3, S4 and S5) were collected in the SRB, from June 2009 to May 2010, which represented one complete hydrological cycle that included the extremes of the rainfall and discharge regimes. In addition, the δ13CDIC values were also characterized in the wet and dry season at all sampling points to verify their seasonal variability. The results reflected the seasonal variation in discharges, water temperatures, and electrical conductivities. Most of the DIC was transported in the wet season at all sampling points, where the less negative δ13CDIC values were characterized. The natural sources of DIC are associated with atmospheric/soil CO2 consumption. The anthropogenic impacts on both [DIC] and δ13CDIC are linked to untreated urban sewage that is discharged directly into the Sorocaba River, as well as to aquatic photosynthesis in the Itupararanga Reservoir. From 1970 to 2020, the modeling proposed in this study indicated that the annual flux of DIC (Friver) varied from 9.0 to 78.7 t km−2 a−1, confirming that the El Niño Southern Oscillation (ENSO) controlled Friver in the SRB, with higher and lower Friver values occurring during strong El Niño (EN) and La Niña (LN) years. The average Friver value was 20 t km−2 a−1, which is higher than those obtained in natural several temperate and tropical watersheds due to the influences of urban areas on [DIC] in the SRB.
Keywords: Brazil; Carbon cycle; Disturbed watersheds; El Niño Southern Oscillation; Tropical climate